Phenomenon Sex Pre-marriage among Adolescents in the District Lembeyan Regency Magetan - Utomo, Ilham Ibnu (Jurnal Health Sains, 2024)
This research describes phenomenon behavior sex pre - wedding among teenagers in the District Lembeyan, Regency Magetan, as well analyze the role of parents in efforts prevention. Research methods use approach qualitative with technique interviews and documentation to teenagers below​ 19-year-olds involved in the behavior, as well as parents and local KUA officers. The result show that behavior sex pre-wedding influenced by relationships No healthy and lacking supervision from parents.​ Parent​ identified as having a role important as educators, role models, supervisors, and counselors in preventing behavior sex pre-wedding. Findings This provides input For increase understanding and action preventive in the field health teenager.